Changing positive and negative affects through music experiences: a study with university students - José Salvador Blasco-Magraner; Gloria Bernabé-Valero; Pablo Marín-Liébana; Ana María Botella-Nicolás (BMC Psychology, 2023)
Abstract Background Currently, there are few empirical studies that demonstrate the effects of music on specific emotions, especially in the educational context. For this reason, this study was carried out to examine the impact of music to identify affective changes after exposure to three musical stimuli. Methods The participants were 71 university students engaged in a music education course and none of them were musicians. Changes in the affective state of non-musical student teachers were studied after listening to three pieces of music. An inter-subject repeated measures ANOVA test was carried out using the Positive and Negative Affect Schedule (PANAS) to measure their affective state. Results The results revealed that: (i) the three musical experiences were beneficial in increasing positive affects and reducing negative affects, with significant differences between the interaction of Music Experiences × Moment (pre-post); (ii) listening to Mahler’s sad fifth symphony reduced more negative affects than the other experimental conditions; (iii) performing the blues had the highest positive effects. Conclusions These findings provide applied keys aspects for music education and research, as they show empirical evidence on how music can modify specific affects of personal experience.